Agrobacterium-mediated transformation of durum wheat (Triticum turgidum L. var. durum cv Stewart) with improved efficiency - He, Y. (Oxford University Press, 2010)
An efficient Agrobacterium-mediated durum wheat transformation system has been developed for the production of 121 independent transgenic lines. This improved system used Agrobacterium strain AGL1 containing the superbinary pGreen/pSoup vector system and durum wheat cv Stewart as the recipient plant. Acetosyringone at 400 μM was added to both the inoculation and cultivation medium, and picloram at 10 mg l(−1) and 2 mg l(−1) was used in the cultivation and induction medium, respectively. Compared with 200 μM in the inoculation and cultivation media, the increased acetosyringone concentration led to significantly higher GUS (β-glucuronidase) transient expression and T-DNA delivery efficiency. However, no evident effects of acetosyringone concentration on regeneration frequency were observed. The higher acetosyringone concentration led to an improvement in average final transformation efficiency from 4.7% to 6.3%. Furthermore, the concentration of picloram in the co-cultivation medium had significant effects on callus induction and regeneration. Compared with 2 mg l(−1) picloram in the co-cultivation medium, increasing the concentration to 10 mg l(−1) picloram resulted in improved final transformation frequency from 2.8% to 6.3%, with the highest frequency of 12.3% reached in one particular experiment, although statistical analysis showed that this difference in final transformation efficiency had a low level of significance. Stable integration of foreign genes, their expression, and inheritance were confirmed by Southern blot analyses, GUS assay, and genetic analysis. Analysis of T(1) progeny showed that, of the 31 transgenic lines randomly selected, nearly one-third had a segregation ratio of 3:1, while the remainder had ratios typical of two or three independently segregating loci.